The Effectiveness of Aromatherapy on Sleep Quality, Anxiety, and Fatigue in Patients Undergoing Hemodialysis : A Systematic Review (Nursing Care Journal, 2024)
Introduction: Aromatherapy is a complementary alternative medicine, its a natural way of treatment for patient undergoing hemodialysis. This study systematically reviews the literature to ensure the effectiveness of aromatherapy on sleep quality, anxiety and fatigue in patients undergoing hemodialysis. Methods: We used “aromatherapy” restricted our search to “sleep quality” and “anxiety” and “fatigue” and used “hemodialysis”, keywords and abstract connected by the Boolean operator “AND”. Search articles in the international database; EBSCO, Science Direct, Scopus, ProQuest, limited to the last 5 years, 2016 to 2020 obtained 15 International Journal. The inclusion criteria to focused aromatherapy just on sleep quality, anxiety, and fatigue, in patient hemodialysis. The article were all RCT design. Other than that is included in exclusion criteria. Results: The aromatherapy that used lavender, rose, and orange essential oil. Frequency of therapy there are for every day until three times a week. During one week until ten months. Intervention with aromatherapy gives good result on sleep quality, anxiety and fatigue in patients undergoing hemodialysis. Conclussions: The results of the reviewed studies shown the beneﬁcial eﬀect of inhalation and massage aromatherapy on sleep quality, fatigue, and anxiety in hemodialysis patients.